Life standards and intergenerational transmission of earnings: a comparative analysis among different family arrangements in Nicaragua - Montoya, Alvaro José Altamirano (2015)
In contrast with other societies, the single mother status is not a new pattern in Latin America, but rather a traditional configuration that reflects historical continuity. For Nicaragua, there is a notion of women being poorer and disadvantaged in relation to men, and thus transmitting their conditions upon their children. In that context, the main objective of this investigation is to analyze, comparatively, the socioeconomic conditions among single mother and biparental families. The research was divided in three articles: the first uses data from the most recent national household survey to compare different socioeconomic conditions among single- mother and biparental families; the second applies the Alkire-Foster (2011) multidimensional poverty methodology to breakdown poverty among those families, using Nicaragua‘s national Demographic and Health Survey (DHS 2011/2012) for that purpose; and finally, article 3 uses the last three national household surveys to understand the patterns of intergenerational earnings mobility, occupational characteristics and income inequality between both family groups. The results show that Nicaraguan households headed by single-mothers have similar socioeconomic conditions as families with both parents. On the other hand, we found that women are more likely to have fewer weakly working hours, which suggests they prioritize occupations that allows them more time allocation in house and child care. In contrast, income analysis revealed a narrowing gender wage gap over the past decade. Using analytical tools that take into account the different dimensions of poverty we found poverty dominance on male-led families over single-mother families and female-led biparental families. These conclusions reflect the resilience and audacity single mothers develop in face of challenges imposed by society. The way forward, though, will need to include men to share household responsibilities in all dimensions, in societies with less asymmetric gender relations and more mutually discussed decisions.